Effektivitas Komite Audit, Dewan Komisaris Independen dan Biaya Audit - Nurjanah, Fitri; Imam Amrozi, Akhmad (E-Jurnal Akuntansi, 2021)
The purpose of this study is to analyze the effect of effectiveness of audit committee and independence board of commissioner on audit fee. This research uses samples of Non-financial companies in Indonesia Stock Exchange (IDX) in 2015-2018. The sampling technique used purposive sampling. The total number of companies used as research samples is 584 companies. Using tools SPSS 20 and testing hypothesis using linear regression. The F test indicates a stable and significant model. R square is 49,4%The result show independence board of commissioner and Effectiveness of audit committee can positively significant effect on audit fee because board of commissioners and audit committee wants a higher audit quality from the auditor. Keywords: Board Of Commissioners; Effectiveness Of Audit Committee; Audit Fee.